Diversity of antimicrobial-resistant bacteria isolated from Australian chicken and pork meat - Dixit, Ojas V. A.; Behruznia, Mahboobeh; Preuss, Aidan L.; O’Brien, Claire L. (Frontiers in Microbiology, 2024)
AnVmicrobial resistant bacteria are frequently isolated from retail meat and may infect humans. To determine the diversity of anVmicrobial resistant bacteria in Australian retail meat, bacteria were cultured on selecVve media from raw chicken (n=244) and pork (n=160) meat samples obtained from all four major supermarket chains in the ACT/NSW, Australia, between March-June 2021. AnVmicrobial suscepVbility tesVng (AST) was performed for 13 criVcally-and 4 highly-important anVbioVcs as categorized by the World Health OrganizaVon (WHO) for a wide range of species detected in the meat samples. A total of 288 isolates underwent whole genome sequencing (WGS), to idenVfy the presence of anVmicrobial resistance (AMR) genes, virulence genes, and plasmids. AST tesVng revealed that, 35/288 (12%) of the isolates were found to be mulVdrug-resistant (MDR). Using WGS data, 232/288 (81%) of the isolates were found to harbour resistance genes for criVcally-or highly-important anVbioVcs. This study reveals a greater diversity of AMR genes in bacteria isolated from retail meat in Australia than previous studies have shown, emphasising the importance of monitoring AMR in not only foodborne pathogenic bacteria, but other species that are capable of transferring AMR genes to pathogenic bacteria.